Under the radar: cancer and the cold war - Leopold, Ellen (New Brunswick, N.J., 2008)
"At the end of the Second World War, a diagnosis of cancer was a death sentence. Sixty years later, it is considered a chronic disease rather than one that is invariably fatal. Although survival rates have improved, the very word continues to evoke a special terror and guilt, inspiring scientists and politicians to wage war against it.